International taxation of services : proceedings of a seminar held in Rio de Janeiro in 1989 during the 43rd Congress of the International Fiscal Association.: proceedings of a seminar held in Rio de Janeiro in 1989 during the 43rd Congress of the International Fiscal Association. (2016) - Unknown
No abstract available